Knockdown of EIF3H inhibits the development and progression of pancreatic cancer by regulating cell proliferation and apoptosis in vitro - Shan, Yuqiang; Kong, Wencheng; Zhu, Akao; Li, Jiangtao; Jin, Huicheng; Zhu, Weiming (Cellular and Molecular Biology, 2022)
Nowadays, pancreatic cancer has been recognized as one of the most fatal malignancies worldwide, the molecular mechanism of which is still not fully understood. In this study, we aimed to uncover the fundamental functions of the eukaryotic translation initiation factor 3H subunit (EIF3H) in the development and progression of pancreatic cancer. Firstly, the results of immunohistochemical (IHC) staining revealed that EIF3H was highly expressed in pancreatic cancer. Moreover, lentiviruses were used to deliver shRNAs into pancreatic cancer cells for silencing EIF3H. Furthermore, the loss-of-function assays demonstrated that knockdown of EIF3H could inhibit the progression of pancreatic cancer cells by reducing proliferation capacity, promoting apoptosis, arresting cell cycle in G2 and suppressing cell migration. In summary, EIF3H may play a critical role in the development and progression of pancreatic cancer, which possesses the potential to act as a therapeutic target for pancreatic cancer treatment.